2007
DOI: 10.1111/j.1600-0846.2007.00180.x
|View full text |Cite
|
Sign up to set email alerts
|

Melanocytic skin lesions and pregnancy: digital dermoscopy analysis

Abstract: The study showed that pregnancy leads to significant modifications in PSL, especially with regard to pigment network, globules and architectural order or disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 20 publications
0
35
0
2
Order By: Relevance
“…It has been shown that these changes linearly increase with the length of pregnancy and are most evident during the third trimester and at the time of delivery. [56][57][58][59] These changes also reverse themselves approximately 3 to 6 months after delivery, and so reexamination of nevi at that time is usually recommended. Since any change during a 3-month interval must be considered suspect, the physiologic changes of nevi should be taken into account when performing shortterm digital follow-up.…”
Section: Commentmentioning
confidence: 99%
“…It has been shown that these changes linearly increase with the length of pregnancy and are most evident during the third trimester and at the time of delivery. [56][57][58][59] These changes also reverse themselves approximately 3 to 6 months after delivery, and so reexamination of nevi at that time is usually recommended. Since any change during a 3-month interval must be considered suspect, the physiologic changes of nevi should be taken into account when performing shortterm digital follow-up.…”
Section: Commentmentioning
confidence: 99%
“…Number of sunburns [8],[11][13] and low latitude [12],[14][18] have also been associated with increased nevus prevalence. Because number of nevi peaks during puberty [1] and nevi are reported to be darker and larger during pregnancy [19],[20], a hormonal influence on nevi may also be speculated. Consistently, melanocytes, the pigment-producing cells, have been shown to express estrogen and androgen receptors [21].…”
Section: Introductionmentioning
confidence: 99%
“…There was also a statistically significant increase in the total dermoscopy score between the first and third trimesters. In a study using digital dermoscopy to evaluate 206 nevi in pregnant patients, excluding those on the breasts, abdomen, and acral regions, 21 lesions were observed between weeks 5 and 8, weeks 39 and 41, and again 1 year after delivery. Multivariate analysis of variance revealed that during pregnancy the pigment network thickens, becoming more prominent, and globules of nevi with a globular pattern darken.…”
Section: Nevi During Pregnancymentioning
confidence: 99%